The Practical Application Of Malakah Theory In The Learning Of Arabic Language/ التطبيق العملي لنظرية الملكة اللغو ية في تعلم اللغة العربية - Haron, Sueraya Binti Che; Abdullah, Nurazzelena; Al Rawahi, Mohammed Mabrook Salim; Alobeidani, Mohammed Juma Mohammed; Ahmat Safri, Norazman (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Learning Arabic requires a practical approach and theory to ensure the desired results. This research explores the theory presented by Ibn Khaldun,